The promising role of miRNAs in radioresistance and chemoresistance of nasopharyngeal carcinoma - Xu, Haoyuan; Li, Wanpeng; Wang, Dehui (Frontiers in Oncology, 2024)
Nasopharyngeal carcinoma (NPC) is a malignant epithelial tumor that develops in the nasopharynx. It has a distinct ethnic and geographical distribution, and emerging evidence suggests that it is an ecological disease. Most patients respond well to radiation combined with chemotherapy as the primary treatment for NPC. However, some patients will eventually develop radio resistance and chemoresistance, resulting in recurrence and metastasis, which is a primary cause of poor prognosis. The processes underlying radio resistance and chemoresistance in NPC are complex and unknown. MicroRNAs (miRNAs) are endogenic non-coding RNA molecules. They play a role in a variety of cell functions as well as development of disease such as cancer. There has been considerable data demonstrating the existence of numerous aberrant miRNAs in cancer tissues, cells, and biofluids, which indicates the importance of studying the influence of miRNAs on NPC. Therefore, this review comprehensively analyzes the elaborate mechanisms of miRNAs affecting the radio resistance and chemoresistance of NPC. Multiple tumor-specific miRNAs can be employed as therapeutic and prognostic biological indicators.